Características da tarefa e características individuais como antecedentes do sucesso de sistemas de informação em saúde: um estudo na saúde pública de Pato Branco - Santos, Marcelo Junior dos (2017)
Information systems (IS) are present in organizations belonging to all sectors, including health organizations. In recent years, an intensification of the implementation of health information systems has been observed. In Brazil, the Ministry of Health has made it compulsory to use electronic medical records. Thus, all municipalities will have to use a system of their own or the one provided by the Ministry. It is required that the systems generate benefits for the organizations, which makes their evaluation indispensable. The success of information systems has been widely studied, having as framework the Delone and Mclean (1992) model. Several studies have sought to confirm or re-specify the model and a more recent interest in the history of IS success is highlighted, such as task and individual characteristics. This work proposes an IS success model, presenting task and individual characteristics as antecedents of the IS success. The model is based on current and relevant studies, compiled by a systematized literature review. After the model proposition, a qualitative research was carried out, through semi-structured interviews with system users, with the purpose of verifying the pertinence of the constructs and assisting in the definition of the variables. Subsequently, a quantitative research was carried out with users of a health information system, where the influence of Information Quality, System Quality and Service Quality on the perception of Individual Impacts was verified through the modeling of structural equations. In addition, task and individual characteristics were proven as antecedents of SI success in the researched context. Another obtained result was the need for training and differential support to different health professional categories.